Answer:
-6 goes inside ( ) since G(-6)=10.
Explanation:
It looks like you are looking for a number such that when you put in the ( ) of G( ) you get 10 as a result.
So let's say you are trying to solve G(b)=10 for b.
Well G(x)=-3x-8 so G(b)=-3b-8.
I just replaced all the x's with b's to find G(b).
Now we are trying to solve G(b)=10 for b.
G(b)=10
-3b-8=10
Add 8 on both sides:
-3b=10+8
Simplify:
-3b=18
Divide both sides by -3:
b=18/-3
Simplify:
b=-6
So G(-6)=10!
Check:
-3(-6)-8
18-8
10
G(-6)=10 is confirmed.
-6 goes inside the G( )=10.